Автоколивна динаміка в математичній моделі метаболічного процесу аеробної бактерії. Вплив циклу Кребса на самоорганізацію біосистеми - Grytsay, V. I.; Medentsev, A. G.; Arinbasarova, A. Yu. (Publishing house "Academperiodika", 2020)
We have modeled the metabolic process running in aerobic cells as open nonlinear dissipative systems. The map of metabolic paths and the general scheme of a dissipative system participating in the transformation of steroids are constructed. We have studied the influence of the Krebs cycle on the dynamics of the whole metabolic process and constructed projections of the phase portrait in the strange attractor mode. The total spectra of Lyapunov exponents, divergences, Lyapunov’s dimensions of the fractality, Kolmogorov–Sinai entropies, and predictability horizons for the given modes are calculated. We have determined the bifurcation diagram presenting the dependence of the dynamics on a small parameter, which defines system’s physical state.